Analisis Pengaruh Harga Kamar Terhadap Penjualan Kamar Di Montigo Resorts Nongsa, Batam - Adeline Tania; Asmawih (Politeknik Sahid, 2021)
This thesis is done in order to find out the room rate variation that will affect the room sales in a hotel. Therefore, the writer would like to examine the problems regarding the room rates offered by Montigo Resorts Nongsa which is have any affect to the room sales in Montigo Resorts Nongsa, Batam. The problem identification that could be found in this research is: How the influence of room rates on room sales at Montigo Resorts Nongsa, Batam and how the effect of the room rates towards the room sales at Montigo Resorts Nongsa, Batam. The research purposed to be achieved through this research are: to find out how the influence of the room rates on the level of room sales at Montigo Resorts Nongsa, Batam also to find out how big the influence of the room rates towards room sales at Montigo Resorts Nongsa, Batam. This test was conducted at Montigo Resorts Nongsa, Batam, with a total population of 50.680 guest and a sample size of 100 respondents. Based on the results of research conducted that the hypothesis that stated there is a positive and significant connection between room rates towards room sales at Montigo Resorts Nongsa, Batam could be proved. The results of the linear regression summary output model is the coefficient of determination (R square) of 0.8711 or 87,1%, it shows that the dependent variable (room occupancy rate) are influenced by independent variables (room rates), while the remaining 12,9% is explained by other variables outside the tested variable in this research. R value of 0.933 (a), indicating that the magnitude of the strong positive relationship between room rates towards room occupancy rate. Seen in the coefficients column of room rate models, there is a sig value of 0.000 whose value is smaller than the probability value of 0.05 (sig. 0.000 < 0.05) and a positive t value of 25.711 and tcount > ttable with a significance level of 5% (25.71 > 1.985, indicating that the room rates variable have a positive and significant relationship towards room sales variable. Advice that could be given by the writer in this research are: The hotel must maintain the quality of products and services provided in order to maintain the level of satisfaction of guests who come to stay for the first time or guests who come to stay again also the hotel should maintain the room rates so that the room sales is maintained or increased stability.